2016
DOI: 10.1016/j.jped.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional evaluation of children with chronic cholestatic disease

Abstract: Evaluation using weight in patients with chronic liver diseases may overestimate the nutritional status due to visceromegaly, subclinical edema, or ascites. Indices that correlate weight and height, such as W/H and BMI, may also not show depletion because of the chronic condition in which there are depletion of both weight and height. TST, AC, and ACM are parameters that better estimate nutritional status and should be part of the management of patients with liver diseases and cholestasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 17 publications
0
16
0
2
Order By: Relevance
“…It has been suggested that liver disease is more likely to cause malnutrition, especially severe malnutrition, than other diseases in children. However, the malnutrition prevalence was lower than in a recent study in Brazil (stunting 50·0 %, underweight 27·3 % and wasting 11·1 %, respectively) ( 5 ) . The difference may be attributed to the course and severity of the liver disease.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…It has been suggested that liver disease is more likely to cause malnutrition, especially severe malnutrition, than other diseases in children. However, the malnutrition prevalence was lower than in a recent study in Brazil (stunting 50·0 %, underweight 27·3 % and wasting 11·1 %, respectively) ( 5 ) . The difference may be attributed to the course and severity of the liver disease.…”
Section: Discussionmentioning
confidence: 62%
“…The human liver is an important regulator of metabolism, storage, synthesis and absorption of nutrients ( 2 ) . Nutritional deficiencies are common among people with chronic liver disease, especially in children ( 3 5 ) . The malnutrition prevalence in children with chronic liver disease may range from 9·1 to 71·1 % depending on the severity of liver disease ( 5 7 ) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Foram encontrados sete artigos com menos de 10 anos de publicação passíveis de comparação com o presente estudo: quatro brasileiros [15][16][17][18] e três internacionais [19][20][21] . Esses estudos utilizaram os índices E/I e/ou DCT/I para a classificação do estado nutricional e os modelos PELD e/ou MELD e/ou o escore Child-Pugh para a classificação da gravidade da doença.…”
Section: Resultsunclassified
“…Já o segundo estudo mostrou prevalência de 50% de desnutrição. Pode-se observar nesses estudos que os escores de gravidade são bem mais elevados que os encontrados nas duas séries do HCPA, demonstrando um estado clínico bem mais comprometido (tabela 3 18 . Dos 91 pacientes avaliados, 25 apresentavam cirrose.…”
Section: Discussionunclassified